Implementation of the Problem Based Learning (PBL) Learning Model in Economics Subjects at Manado High School - Tamboto, Henry J.D.; Taroreh, Johny; Wuisang, Jerry RH; Sualang, Marsel (PT. Riset Press International, 2025)
This study explores the implementation of the Problem Based Learning (PBL) model in economics subjects at Manado High School. The objective of the research is to examine how PBL influences students' learning experiences, critical thinking, and engagement in economic topics. Using a qualitative descriptive method, data were collected through interviews with teachers and students, classroom observations, and document analysis. The results indicate that PBL enhances students’ problem-solving abilities, promotes active participation, and encourages collaboration in learning. Teachers reported that students became more motivated and better understood economic concepts when learning was contextualized through real-world problems. However, several challenges were identified, including time constraints, varying levels of student preparedness, and the need for teacher training. Overall, the findings suggest that PBL is an effective approach to teaching economics and has the potential to improve the quality of education when implemented with appropriate support and resources.